Efeitos da infusão das células-tronco mesenquimais em modelo animal de resistência insulínica e diabetes tipo 2 - Bueno, Patricia de Godoy (2014)
Type 2 Diabetes Mellitus (DM2) is associated with insulin resistance and dysfunction of pancreatic β cells. The regenerative cellular therapy, in particular with multi/pluripotent cells has been investigated as a potential therapeutic strategy for T2DM. Among them, mesenchymal stem cells (MSCs) due to their immunoregulatory role are important therapeutic candidates. The purpose of this study was to investigate the effect of multiple infusions of MSCs on blood glucose, insulin resistance and morphometry of the pancreatic islets of diabetic mice induced by high fat diet. Swiss mice were fed a standard diet or a high fat diet for eight weeks. Soon after, the diabetic animals were divided into diabetic group and transplanted MSCs group. The transplanted mice received 4 intraperitoneal infusions of cells (5-8 x 106 MSCs resuspended in buffer). Fasting plasma glucose (FPG) was determined weekly and glucose tolerance tests (GTT) and insulin (ITT) were performed at 1 , 2 , 3 , and 4 months after the infusions of MSCs. Four months after infusion of the MSCs, the animals were decapitated and the pancreas and the serum were collected for analysis. The animals that received MSCs were classified as responders (FPG < 180mg/dL) or non-responders (FPG > 180mg/dL). According to this criterion, 72.2 % and 27.8 % of transplanted animals were classified as responders and non-responders, respectively. Responders showed a significant decrease in GJ seven weeks after the infusion of MSCs compared with untreated diabetic group. Four months after MSCs, responders showed a significant decrease of GTT and ITT areas under the curve (AUC), compared with untreated diabetic group. Serum insulin concentration was significantly higher in diabetic animals compared with the control group. There was no statistical difference in the total area and volume of islet β cells in diabetic animals and responders and non-responders. The relative volume of α cells was significantly lower in diabetic animals and responders, compared to the control group and significantly higher in non-responders transplanted animals compared to diabetic animals. Apoptosis of islet cells was significantly greater in diabetic animals and non-responders, and significantly lower in responders, compared with the control and diabetic groups, respectively. Islet cell proliferation was significantly lower in diabetic animals compared to the control group. However, islet cell proliferation was not statistically different in transplanted animals compared to controls and diabetic animals. There was a positive correlation between apoptosis of the islet cells and fasting glucose and AUC of GTT and ITT, and a negative correlation of the proliferation of the islet cells and fasting glucose. The results demonstrate that multiple infusions of MSCs can decrease fasting glucose and apoptosis in pancreatic islets and increase insulin sensitivity in diabetic rats induced by high fat diet.